Human Resources Management Using Temporary Employment – Case Study - Bąk-Grabowska, Dominika (Acta Universitatis Lodziensis. Folia Oeconomica, 2013)
This article shows a case study of the company which employs temporary agency workers. The actions taken within the human resource management process have been recognized. The division of competences between the agency and the user firm has also been identified. The evaluation of the analyzed process has been based on the modern conceptions and models of human resources management connected with flexible employments.